Rancang Bangun Aplikasi Transliterasi Aksara Latin menjadi Aksara Sasak Menggunakan Algoritma Rule Based Berbasis Android - Putu Wahyu Pratama; Arik Aranta; Fitri Bimantoro (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2021)
The Sasak script is one of the cultural heritage of the Sasak people on the island of Lombok. But lately, the Sasak script has begun to be rarely used among the Sasak people, especially among the younger generation. If this continues, the existence of the Sasak script is threatened with extinction. One of the efforts in preserving the Sasak script is digitizing the Sasak script to digital technology devices by utilizing Unicode. In this research, the author will make an android-based transliteration application and develop a rule-based algorithm that refers to the rules of the Sasak script. The string replacement method with hexadecimal addressing derived from the UTF-16 Unicode is used to adjust the Latin characters with the writing rules of the Sasak script. Digital writing of the Sasak script using 47 symbols from Unicode Balinese block on “1B00-1B7F”. To transliterate Latin script into the Sasak script, the author has developed 1704 rule-based rules to apply all the rules of writing the Sasak script. The accuracy test towards on 3 data sources, namely testing of street signage in Mataram City obtained an accuracy value of 97.20% from 250 data test, testing of